Markets and power in digital capitalism / Philipp Staab ; translated by Meredith Dale. - Staab, Philipp (Manchester University Press, 2024)
Philipp Staab takes readers on a thought-provoking journey through the virtual realm, exploring how digital surveillance and evaluation practices have infiltrated every aspect of our lives. Staab's compelling analysis challenges us to confront the realities of surveillance capitalism and the urgent need to address the inequities it perpetuates.